MEMBANGUN KEPEMIMPINAN DELIBERATIVE DI ERA VUCA (VOLATILITY, COMPLEXITY, AND AMBIGUTY) - Sri Weningsih; Chamid Sutikno (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Leadership is an effort made to regulate and direct in achieving good organizational order. Developments in organizational activities are increasingly complex, marked by the existence of needs that must be met, such as plans or strategies as a form of adaptive approach to leaders in an organization. With an adaptive leadership style like this one is able to update situations and conditions that allow dynamic actions to be taken by actors in realizing the success of existing goals and an unknown organizational climate in the future. Development of quality human resources in terms of leadership as a form of an organization's efforts to face the digital era, especially in the era of VUCA (Volatile, Uncertainty, Complexity, Ambiguity) and global competitiveness. The VUCA era is a state in which changes occur full of uncertainty in the social order and organization. To deal with this situation, organizations need qualified and competent leaders, especially transformational types. One model of leadership that is able to build various kinds of interests is the deliberative approach. One model of leadership that is able to build various kinds of interests is the deliberative approach. The deliberative leadership approach is a synthesis of an elitist leadership pattern and a bottom up model, deliberative leadership combines a leadership model in achieving goals in organizations that are more dynamic and always ready to respond to any social changes that are experienced. Keywords; Deliberative, Leadership, VUCA Era